PENGEMBANGAN APLIKASI SOFTWARE MULTIMEDIA DALAM PEMBELAJARAN BAHASA INGGRIS TEKNIK PADA PRODI PENDIDIKAN TEKNIK BANGUNAN - Ayyasy, Firas; Anisah; Daryati (Jurnal Pendidikan Teknik dan Vokasional, 2022)
This research was developed using a research and development (R&D) model that refers to the Lee & Owens Instructional design model so that it can develop learning media in Engineering English courses in the form of Android-based multimedia software applications, thus facilitating access and student learning activities in the class as well as outside of the class. Lee and Owens' model consists of five stages, namely assessment/analysis, design, development, implementation, and evaluation. The data analysis technique in this study used a questionnaire to collect data from needs analysis, linguist validation, and product evaluation. The results of the media development research are 13 meetings of Android-based multimedia software application products that have been validated by linguists who obtained 85.75% results and fall into the very feasible category. The conclusion that can be drawn is that the Android-based multimedia software application is grammatically feasible, but it should be validated by a material expert before the developed media can be used in Technical English for Engineering courses.